Contribution of Learning Motivation and Learning Attitude to Student Learning Outcomes in Digital Simulation Courses - Mulya Melda; Hasan Maksum; Eko Indrawan; Dori Yuvenda (STAI Miftahul Ula Nganjuk, 2021)
The background of this research is the low value of students in digital simulation courses of Informatics Engineering education and Computer Education FKIP UBH. Based on the data of the last three years, that the value of students under 70 reached 50%. The purpose of this study is to find out how much contribution: (1) motivation to learn on student learning outcomes in digital simulation courses ptik study program FKIP UBH Padang City, (2) attitude of learning to the results of learning in digital simulation courses ptik study program FKIP UBH Padang City, and (3) learning motivation and attitude of learning together to the results of learning students in the course Digital Simulation study program PTIK FKIP UBH Padang City. This research is quantitative research with correlational type. The research population was 39 students. The sampling technique uses the Total Samplingtechnique, which means that the sample has the same number as the population. Data on learning motivation and learning attitudes were obtained through questionnaires using the Likertscale, while data on student learning outcomes in Digital Simulation courses were obtained from the final score of the even semester of FY 2019/2020. The data in the analysis uses statistical methods with the help of SPSS software version 17. The results of the data analysis showed that (1) there was a positive and significant relationship of learning motivation to student learning outcomes with a correlation coefficient of 0.531, thus contributing 28.20%. (2) Then, there is a positive and significant relationship between the attitude of learning towards student learning outcomes with a correlation coefficient of 0.559, thus contributing 31.25%. (3) Furthermore, there is a positive and significant relationship between learning motivation and learning attitudes together with student learning outcomes with a correlation coefficient of 0.657 thus contributing 43.16%. This proves that learning motivation and learning attitudes contribute strongly in improving student learning outcomes in the Digital Simulation course of PTIK FKIP UBH study program in Padang City.